Indoleamine 2, 3-Dioxygenase 1 Mediates Survival Signals in Chronic Lymphocytic Leukemia via Kynurenine/Aryl Hydrocarbon Receptor-Mediated MCL1 Modulation - Atene, Claudio Giacinto; Fiorcari, Stefania; Mesini, Nicolò; Alboni, Silvia; Martinelli, Silvia; Maccaferri, Monica; Leonardi, Giovanna; Potenza, Leonardo; Luppi, Mario; Maffei, Rossana; Marasca, Roberto (Frontiers in Immunology, 2022)
The indoleamine 2,3-dioxygenase 1 (IDO1) metabolic circuitry, comprising the first tryptophan (Trp) catabolite L-kynurenine (Kyn) and the aryl hydrocarbon receptor (AHR), has emerged as a mechanism of cancer immune evasion. Here, we investigated the functional role of the IDO1/Kyn/AHR axis in chronic lymphocytic leukemia (CLL). Our data show that CLL cells expressed an active form of the IDO1 enzyme and microenvironmental stimuli can positively modulate its expression. Interferon (IFN)-γ induces IDO1 expression through the Jak/STAT1 pathway and mediates Kyn production concomitantly with Trp consumption in CLL-conditioned media, while INCB018424 (ruxolitinib), a JAK1/2 inhibitor, impaired both effects. To characterize the involvement of IDO1 in leukemic cell maintenance, we overexpressed IDO1 by vector transfection measuring enhanced resistance to spontaneous apoptosis. IDO1 pro-survival influence was confirmed by treating CLL cells with Kyn, which mediated the increase of induced myeloid leukemia cell differentiation protein (MCL1). Conversely, AHR silencing or its blockade via CH-223191 improved the apoptosis of leukemic clones and mitigated MCL1 expression. Moreover, Kyn-treated CLL cells are less affected by the pro-apoptotic effect of ABT-199 (venetoclax), while CH-223191 showed synergistic/additive cytotoxicity with this drug. Lastly, targeting directly MCL1 in CLL cells with AMG-176, we abrogate the pro-survival effect of Kyn. In conclusion, our data identify IDO1/Kyn/AHR signaling as a new therapeutic target for CLL, describing for the first time its role in CLL pathobiology.